Effect of CRP and lactate clearance in predicting outcome of emergency abdominal surgeries - Pandey, Vinod Kumar; Singh, Rahul; Nagarwal, Neeraj; Singh, Vaibhav; Singh, Santosh Kumar (International Surgery Journal, 2018)
Background: Emergency abdominal condition had good prognosis if they diagnosed early and had better prognosis. Many biological parameters were considered to reduce postoperative complications. This study aims to study the effects of CRP and 24-hour lactate clearance on morbidity and mortality of patients undergoing emergency abdominal surgery. Methods: All the patients undergone surgery for emergency abdominal conditions over a period of 1 year were included. Patient age of below 15 years and above 70 years were excluded. Results: In the present study of 86 patients, patients whose preoperative CRP level <150 mg/dl and preoperatively CRP >150 mg/dl had mortality of 1 and 9 patients respectively (p = 0.049), wound discharge among 12 and 9 patients respectively (p = 0.113), wound dehiscence among 7 and 9 patients respectively (p = 0.909) and respiratory complications among 2 and 11 patients respectively (p = 0.049). In the present study of 86 patients, patients whose 24 hour lactate clearance of <10% and >10% had mortality of 4 and 3 patients respectively (p = 0.0003), wound discharge among 5 and 16 patients (p = 0.119), wound dehiscence among 5 and 11 patients (p = 0.023), respiratory complication among 5 and 8 patients (p = 0.002), prolonged ileus among 3 and 3 patients respectively (0.007). Conclusions: Preoperative CRP level >150 mg/l associated with higher chances of mortality, respiratory complication and postoperative ileus. 24-hour lactate clearance < 10 % associated with higher chances of mortality, wound dehiscence, respiratory complication and postoperative ileus.